Research on Tax Legal Issues of Virtual Property - Yao, Xiangwu (International Journal of Social Sciences and Public Administration, 2024)
The rapid development of virtual property has become an important part of digital economy and virtual economy. The economic activities of virtual property are increasingly prosperous, and the economic benefits brought by virtual property cannot be underestimated. However, while virtual property-related income is growing, it is difficult for them to be included in the scope of tax collection and management by tax authorities. Starting from the analysis of the legal basis of virtual property, this paper explores the essence and classification of the tax law of virtual property, analyzes the problems existing in the current tax law and the difficulties faced by tax collection and management, and explores the construction of Chinese-style modern virtual property tax law norms and collection and management systems from two aspects of legislation and law enforcement.